Fluoroscopy of the Elbow: A Cadaveric Study Defining New Standard Projections to Visualize Important Anatomical Landmarks. Issue 2 (April 2021) - Müller, Sebastian A.; Adolfsson, Lars; Baum, Cornelia; Müller-Gerbl, Magdalena; Müller, Andreas M.; Rikli, Daniel
Abstract : Background: Despite new 3-dimensional imaging modalities, 2-dimensional fluoroscopy remains the standard intraoperative imaging modality. The elbow has complex anatomy, and defined standard fluoroscopic projections are lacking. Therefore, the aim of this study was to define standard projections of the elbow for intraoperative fluoroscopy. Methods: This study consisted of 2 parts. In part I, dissected cadaveric elbows were examined under fluoroscopy, and their radiographic anatomical features were assessed, with focus on projections showing defined anatomical landmarks. In part II, projections from part I were verified on entire cadavers to simulate intraoperative imaging. Standard projections for anteroposterior (AP) and lateral views as well as oblique and axial views were recorded. Results: Eight standardized projections could be defined and included 3 AP, 1 lateral, 2 oblique, and 2 axial views. By applying these specific projections, we could visualize the epicondyles, the trochlea with its medial and lateral borders, the capitellum, the olecranon, the greater sigmoid notch, the coronoid process including its anteromedial facet, the proximal radioulnar joint with the radial tuberosity, and the anterior and posterior joint lines of the distal part of the humerus. These standard projections were reliably obtained using a specific sequence. Conclusions: Knowledge about radiographic anatomy and standard projections is essential for visualizing important landmarks. With the presented standard projections of the elbow, important anatomical landmarks can be clearly examined. Thus, fluoroscopic visualization of anatomical fracture reduction and correct implant placement should be facilitated. Clinical Relevance: This basic science cadaveric study defines fluoroscopic standard projections of the elbow essential for visualization of anatomical landmarks during surgery.